Activating mutations of GNAS and KRAS in cystic fluid can help detect intraductal papillary mucinous neoplasms of the pancreas. (March 2015) - Frampton, Adam E; Stebbing, Justin; Gall, Tamara MH; Silver, Benjamin; Jiao, Long R; Krell, Jonathan
<x xml:space="preserve">Abstract</x> Evaluation of: Singhi AD, Nikiforova MN, Fasanella KE, et al. Preoperative GNAS and KRAS testing in the diagnosis of pancreatic mucinous cysts. Clin. Cancer Res. 20(16), 4381-9 (2014). Intraductal papillary mucinous neoplasms (IPMNs) of the pancreas have a risk of malignant transformation following an adenoma–carcinoma sequence. Surgical resection is often required, especially for main pancreatic duct IPMNs (MD-IPMNs). There is an urgent need for novel biomarkers to reliably differentiate IPMNs from more benign pancreatic cysts and therefore avoid unnecessary surgery. DNA sequencing has demonstrated that guanine nucleotide binding protein alpha stimulating (GNAS) activity polypeptide 1 mutations play a driving role in IPMN development. GNAS mutations have been shown to be highly specific for IPMNs, whereas oncogenic KRAS mutations have been associated with mucinous differentiation. The evaluated article by Singhi et al. helps to define the role of these mutations as biomarkers in preoperative endoscopic ultrasound fine-needle aspiration samples for detecting IPMNs. They found that the presence of a GNAS and/or a KRAS mutation was highly specific and sensitive for IPMNs.